How vocational education teachers and managers make sense of career guidance. Issue 2 (4th March 2022) - Magee, Martha; Kuijpers, Marinka; Runhaar, Piety
ABSTRACT: Efforts to create career learning environments which provide students with work experience, skills for making choices and career guidance dialogues, appear to stagnate in vocational education and training (VET) institutions in the Netherlands. In this case study we explore how teachers and their managers make sense of career guidance. We found varying views of career guidance, which may be contributing to the stagnation. Dialogue between teachers and managers is crucial in coming to a collective sense-making of career guidance, and a transformational management style seems to instigate sense-making and ultimately change. A collective sense-making of career guidance may be an area that needs to be examined for new possibilities of transforming behaviours relevant to providing career guidance to students.